Differentiation Inductions Altered Telomere Length and Telomerase Activity in Human Dental PulpDerived Mesenchymal Stem Cell - Hyeon-Jeong Lee; Ryoung-Hoon Jeon; Byung-Joon Park; Si-Jung Jang; Sung-Lim Lee; Gyu-Jin Rho; Seung-Joon Kim; Won-Jae Lee (The Korean Society of Animal Reproduction and Biotechnology, 2019)
Telomeres are known as a specialized region in the end of chromosomes to protect DNA destruction, but their lengths are shortened by repetition of cell division. This telomere shortening can be preserved or be elongated by telomerase and TERT expression. Although a certain condition in the cells may affect to the cellular and molecular characteristics, the effect of differentiation induction to telomere length and telomerase activity in mesenchymal stem cells (MSCs) has been less studied. Therefore, the present study aimed to uncover periodical alterations of telomere length, telomerase activity and TERT expression in the dental pulp-derived MSCs (DP-MSCs) under condition of differentiation inductions into adipocytes and osteoblasts on a weekly basis up to 3 weeks. Shortening of telomere was significantly (p < 0.05) identified from early-middle stages of both differentiations in comparison with undifferentiated DP-MSCs by non-radioactive chemiluminescent assay and qRT-PCR method. Telomere length in undifferentiated DP-MSCs was 10.5 kb, but the late stage of differentiated DP-MSCs which can be regarded as the adult somatic cell exhibited 8.1-8.6 kb. Furthermore, the relative-quantitative telomerase repeat amplification protocol or western blotting presented significant (p < 0.05) decrease of telomerase activity since early stages of differentiations or TERT expression from middle stages of differentiations than undifferentiated state, respectively. Based on these results, it is supposed that shortened telomere length in differentiated DP-MSCs was remained along with prolonged differentiation durations, possibly due to weakened telomerase activity and TERT expression. We expect that the present study contributes on understanding differentiation mechanism of MSCs, and provides standardizing therapeutic strategies in clinical application of MSCs in the animal biotechnology.